Appraisal of non-destructive in situ techniques to determine moisture- and salt crystallization-induced damage in dolostones. (1st August 2022) - Fort, R.; Feijoo, J.; Varas–Muriel, M.J.; Navacerrada, M.A.; Barbero-Barrera, M.M.; De la Prida, D.
Abstract: The characterisation of both surface and subsurface pathologies (position, depth, width, …) that affects the porous materials used in building constructions, once in service, is important to establish the most suitable intervention strategy. In this sense, the use of non-destructive techniques allows the analysis of different properties without affecting the material. The present study shows the accuracy of different non-destructive in situ techniques, such as: electrical conductivity and capacitance, infrared thermography, ultrasonic pulse velocity, sound absorption, and electrical resistivity tomography, applied on dolostone ashlar stones outer façade of a sixteenth-century belltower, affected by moisture and salt induced decay. The joint analysis of the results obtained with different techniques substantially improves the interpretation and characterisation of the detected pathologies, as they complement each other perfectly. Electrical resistivity tomography, which delivers resistivity cross-sections, yields very good results in detecting subsurface pathologies, and sound absorption is particularly useful for stone surfaces. In both cases, the frequency of the electric field and that of the acoustic emission to detect the extent of damage must be established in advance. The joint study of electrical conductivity and capacitance determines the degree of moisture/salts, both at the surface and subsurface, in the materials tested, one of the main causes of scaling and flaking in stony materials. However, the petrological characteristics of the materials used and the identification of the saline phases present must be known in advance to make a correct interpretation of the results. Highlights: Hygroscopicity and salt deliquescence affect results. A number of non-destructive in situ tests deliver closely correlated results. Electrical conductivity and capacitance detect moisture and salts complementarily. Electrical resistivity tomography is effective in detecting subsurface pathologies. Impedance testing maps surface decay from absorption coefficient measurements.